2024
DOI: 10.7150/ijms.76817
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into Prokineticin 1 Role in Pregnancy-related Diseases

Xi-Xi Cheng,
Ming-Qing Li,
Ting Peng

Abstract: Prokineticin 1 (PROK1) is a secreted protein involved in a range of physiological activities such as cell proliferation, migration, angiogenesis, and neuronal cell proliferation. Emerging evidences show that PROK1/PROK receptors (PROKRs) are expressed by trophoblasts, and decidual stroma cells at the maternal-fetal interface. PROK1 plays a critical role in successful pregnancy establishment by regulating the decidualization, implantation and placental development. Dysregulation of prokineticin signaling has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The results demonstrate that MRAP2, acting as an allosteric regulator, modulates PKR2-induced β-arrestin-2 recruitment. This study may allow for the identification of allosteric sites as new specific targets for potential drugs useful for the treatment of the different pathologies correlated with prokineticin, especially obesity [5,[31][32][33][34][35][36][37]. Recently, it has been demonstrated that PK2, binding to prokineticin receptor 1 (PKR1), acts as an adipokine and reduces food intake and adipose tissue proliferation via the hypothalamic arcuate nucleus (ARC)-melanocortin system [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrate that MRAP2, acting as an allosteric regulator, modulates PKR2-induced β-arrestin-2 recruitment. This study may allow for the identification of allosteric sites as new specific targets for potential drugs useful for the treatment of the different pathologies correlated with prokineticin, especially obesity [5,[31][32][33][34][35][36][37]. Recently, it has been demonstrated that PK2, binding to prokineticin receptor 1 (PKR1), acts as an adipokine and reduces food intake and adipose tissue proliferation via the hypothalamic arcuate nucleus (ARC)-melanocortin system [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate that MRAP2, acting as an allosteric regulator, modulates PKR2induced β-arrestin-2 recruitment. This study may allow for the identification of allosteric sites as new specific targets for potential drugs useful for the treatment of the different pathologies correlated with prokineticin, especially obesity [5,[31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%